A study on sacred geometry Exploring divine elements and patterns of Spanish colonial era catholic churches in the Visayas and Mindanao for religious architecture - Gonzaga, Camela J.; Songcayauon, Ryan C. (2018)
Sacred Geometry involves sacred universal patterns used in the design of all things in the universe, most often seen in sacred architecture and sacred art using the principles of the proportional roots. The purpose of this research is to provide a method of analysis of sacred spaces such as churches through sacred geometry, examining how geometric features in nature are integrated and contributed to the practical design of sacred structures. Forty-one Spanish colonial era churches in the Visayas and Mindanao were studied. Through semiology, the assessment of human condition, form, architectural reality, sacred geometry, and meaning were studied. Comparative visual analysis was used to categorize the persistent architectural elements and sacred geometry pattern mapping was done to validate the application of these patterns. Photographs and CADD software in scaling for the accuracy of measurements were used. Information about the architectural character and history of the studied churches was also provided. The study on the application of sacred geometry on the Spanish colonial era churches, is an exploratory process of incorporating symbolisms of the Christian belief manifested in shapes and patterns as basis in architectural design. The results validated and identified the common sacred geometry patterns that shaped the church building industry of colonial era churches in the Visayas and Mindanao, specifically on the floor plan and fac?ade. The corresponding symbolism of the patterns in line to the Christian belief were listed. These results were translated into church design guidelines. Further studies can be done with fractal geometry validation to study the application of Christian art and nature forms on church details. A study on exploring innovative geometrical patterns to church architecture in the context of the present time and need can also be done to track the evolution of these geometric patterns throughout the course of Roman Catholic Church building.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2018